Model Pengelolaan Kelas Rangkap pada Anak PMI di Sanggar Bimbingan PERMAI Penang Malaysia - AlMaula, Hubba Lillah; Shufania, Isabella Putri; Soleha, Nadya Zulfi; Kalusa, Nisrina Nitakaini; Andini, Rahma Putri; Prihantini, Prihantini (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Education plays a strategic role in improving the quality of human resources while ensuring equal access to learning opportunities. However, teacher shortages remain a significant challenge, particularly for marginalized communities such as the children of Indonesian Migrant Workers (PMI) in Malaysia. This condition has led to the adoption of multigrade teaching, in which a single teacher is responsible for two or more grade levels within one classroom. This study aims to describe the strategies for managing multigrade classes at Sanggar Bimbingan PERMAI, Penang, as an adaptive response to limited educational resources. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with teachers and administrators, and documentation, then analyzed using Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that multigrade class management was carried out through a combination of flexibility and structured routines, utilizing strategies such as parallel teaching, independent learning activities, peer tutoring, and fair assessment. The main challenges include limited time, restricted classroom space, and heavy teacher workload. Nevertheless, multigrade practice was found to foster student independence, collaboration, and social responsibility. These findings highlight that multigrade teaching is not merely a response to teacher shortages but also holds potential as an inclusive pedagogical model relevant to both formal and non-formal education contexts.